Evaluation of Facial Development of Children with Dental Fluorosis by Björk's Analysis - Alev Aksoy-Doğan; Pınar Bolpaça (Galenos Yayinevi, 2008)
The purpose of this study was to examine the changes of facial dimensions of patients with dental fluorosis in İsparta at the age of 12±1 and 21±1 and compare the results with Turkish norm values by using cephalometric tracing method. Björk's facial development analysis was used as the cephalometric tracing method. The subjects for this study consisted of 36 children of age 12±1 (male:15, female:21) and 41 young adults of age 21±1 (male:20, female:21). Dental fluorosis of the study group was classified using Thylstrup and Fejerskov Fluorosis Index clinically. The mean Fluorosis Index result was 5.39±2.05. Statistical evaluation in between 12±1 and 21±1 age groups was done by Student t test analysis. Marked age-related changes occur in several angular and linear measurements related with facial development very similar to normal growth. Males consistently demonstrated significantly larger values for maxillary and mandibular prognatism and had larger changes than females between 12±1 and 21±1 years of age. Severely less increment of ramus height (Arkk) causes curiosity on the effect of flourosis on condylar growth. The craniofacial morphology at the ages of 12±1 and 21±1 can be regarded as normative cephalometric standards for individuals with dental fluorosis in Isparta.